2016
DOI: 10.1111/jvim.14365
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Diabetes Mellitus among 193,435 Cats Attending Primary‐Care Veterinary Practices in England

Abstract: BackgroundDiabetes mellitus (DM) is a common endocrine disease of cats. The prevalence of DM in cats in England is not well‐defined.Hypothesis/ObjectivesTo estimate the prevalence and identify risk factors for DM in a large population of cats attending primary‐care practices.AnimalsA cohort of 193,563 cats in the VetCompass Programme attending 118 primary‐care practices in England.MethodsCross‐sectional analysis of cohort clinical data. Data were extracted covering September 1st 2009 and August 31st 2014. Peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 54 publications
1
54
2
Order By: Relevance
“…The only difference identified between groups was that DM‐affected cats weighed significantly more than did normal control cats. This finding is consistent with previously published reports of increased body weight being a risk factor for DM development …”
Section: Discussionsupporting
confidence: 94%
“…The only difference identified between groups was that DM‐affected cats weighed significantly more than did normal control cats. This finding is consistent with previously published reports of increased body weight being a risk factor for DM development …”
Section: Discussionsupporting
confidence: 94%
“…Adi ponectin has a negative dose-response association with type 2 diabetes mellitus in humans (Li et al 2009) and cats (Ishioka et al 2009, Tvarijonaviciute et al 2012, Zapata et al 2017. Sev eral studies found positive associations between diabetes mellitus and increased bodyweight or BCS (Scarlett & Donoghue 1998, Lund et al 2005, Prahl et al 2007, O'Neill et al 2016, Öhlund et al 2018. Interestingly, only cats with BCS of 8 of 9 had sig nificantly higher odds of diabetes mellitus compared to cats with BCS of 5 in the current study.…”
Section: Diabetes Mellitusmentioning
confidence: 42%
“…All the veterinarians who had practised in the clinic were trained to use the Purina 9point BCS chart (Fig 1). Assuming equal sample size for seven groups (BCS of 1/2, 3, 4, 5, 6, 7 and 8/9), 97 cats for each BCS group would be required to have 80% power to detect a prevalence of diabetes mellitus at 0•17, 0•29, 0•64, 1•03, 1•99, 4•24 and 5•16% in each group (O'Neill et al 2016), respectively, with a chisquared test (twosided, α=0•05). The extracted prevalence was based on the weight of cats instead of the BCS (O'Neill et al 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations